TRAINING OF PEDAGOGUES TO ADDRESS SEXUALITY AT SCHOOL: CHALLENGES, STRATEGIES AND PEDAGOGICAL PERSPECTIVES - Domingos de Lira, Bruno (Revista Gênero e Interdisciplinaridade, 2025)
This scientific article explores the training of educators to address sexuality in schools, emphasizing the challenges, strategies and pedagogical perspectives. Sexuality constitutes an integral aspect of human development and its understanding in schools needs to be approached with sensitivity and adequate knowledge. This study aims to identify the challenges faced by educators in their training and practice when dealing with sexuality in the school environment. We investigate how the psychological and emotional aspects related to sexuality influence students’ learning and development, in addition to providing fundamental support to educators. Through a detailed analysis of effective pedagogical strategies, the article offers a comprehensive view of how formal education can integrate sexuality in a constructive and positive way into the educational curriculum. By adopting an interdisciplinary approach and supported by recent research in the area of ​​educational psychology, we aim to build a theoretical and practical framework that assists in the training of educators, addressing issues of sexuality with confidence and competence. We conclude with a reflection on future perspectives and possibilities for continuous improvement in the training of pedagogues, with a view to creating a more inclusive school environment that is aware of the complexities of human sexuality.